2005
DOI: 10.1007/s11214-005-3834-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause and Boundary Layer

Abstract: International audienceNot Availabl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 143 publications
4
38
1
Order By: Relevance
“…One branch lies in cylindrically symmetric plasma systems which are ubiquitously observed in geo-space by a multitude of measurements from, e.g., ground-based imagers ( Pimenta et al 2001), rockets (Earle et al 1989;Moore et al 1996), and satellites (Pickett et al 2004;Vaivads et al 2004;De Keyser et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One branch lies in cylindrically symmetric plasma systems which are ubiquitously observed in geo-space by a multitude of measurements from, e.g., ground-based imagers ( Pimenta et al 2001), rockets (Earle et al 1989;Moore et al 1996), and satellites (Pickett et al 2004;Vaivads et al 2004;De Keyser et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Here we briefly outline some of the essential results and features of magnetopause structure and dynamics. The magnetopause itself has been the subject of numerous more-detailed reviews and monographs (e.g., Lundin 1988;Song et al 1995;Paschmann 1997;Sibeck et al 1999b;Farrugia et al 2001;De Keyser et al 2005;Phan et al 2005a;Lavraud et al 2011;Hasegawa 2012), and the interested reader is invited to consult these articles and reviews for more information.…”
Section: Basic Structure Of the Magnetopausementioning
confidence: 99%
“…The transport of plasma across a magnetopause produces mixed plasma regimes adjacent to the interface that are known as boundary layers. Spacecraft observations have revealed that the low-latitude boundary layer (LLBL) earthward of the magnetopause contains a mixture of magnetospheric and magnetosheath plasma with a generally tailward bulk flow (see, e.g., the review by De Keyser et al 2005). Observations have also revealed that although the layer is a quasi-permanent feature of the terrestrial magnetosphere, its properties are also highly variable (Masters et al 2011 and references therein).…”
Section: High-latitude Solar Wind-magnetosphere-ionosphere Couplingmentioning
confidence: 99%